2008
DOI: 10.1016/j.cell.2008.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin Complex Promotes Transcriptional Termination between Convergent Genes in S. pombe

Abstract: Transcription analyses reported in these studies reveal that convergent genes in S. pombe generate overlapping transcripts in the G1 phase of the cell cycle. We show that this double-strand (ds) RNA induces localized RNAi (Dicer and RITS) dependent transient heterochromatin structures including histone H3 lysine 9 trimethylation marks and Swi6 association. Consequently cohesin is recruited to these chromosomal positions through interaction with Swi6. In G2, localized cohesin is further concentrated into the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
216
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(228 citation statements)
references
References 31 publications
8
216
4
Order By: Relevance
“…The data suggest that transcription prevents the accumulation of functional cohesin complexes on the URA3 excision cassettes. The results are consistent with previous reports of transcription altering the distribution of cohesin on chromatin (15,16,(20)(21)(22)40).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The data suggest that transcription prevents the accumulation of functional cohesin complexes on the URA3 excision cassettes. The results are consistent with previous reports of transcription altering the distribution of cohesin on chromatin (15,16,(20)(21)(22)40).…”
Section: Resultssupporting
confidence: 83%
“…Work with representative RNA polymerase II genes showed that transcription causes cohesin to move from initial positions on ORFs, often leading to enrichment at downstream regions (15,16,(20)(21)(22). Mobilization by an advancing RNA polymerase has been invoked to account for the redistribution.…”
mentioning
confidence: 99%
“…In addition, it is possible that chromatin remodeling factors facilitate the recruitment of factors that are directly involved in termination. This is illustrated by a recent study in S. pombe showing that Swi6 (human HP1) recruits cohesin to the intergenic region of convergent genes, which forces RNAPII to terminate by blocking RNAPII elongation (Gullerova and Proudfoot 2008). While ChIP analysis in HeLa cells showed an association of several proteins involved in chromatin remodeling with the entire transcription unit, including the region downstream from the poly(A) site (Venkataraman et al 2005), detailed studies of the possible role of chromatin remodeling factors in mammalian termination are necessary to better understand the exact function and generality of chromatin in termination.…”
Section: Rnapii Termination and Chromatin Remodeling Factorsmentioning
confidence: 98%
“…Fission yeast cohesin has an important function in regulating transcriptional termination of convergently transcribed genes. 41 In fact, cohesin is loaded in the termination region of these genes already in G 1 . Therefore, it is conceivable that some cohesin protection mechanism is in place.…”
mentioning
confidence: 99%